Optimizing Digital Literacy Through Problem-Based Learning Models to Improve Student's Critical Thinking Skills - Gitadewi, Aisyah Jiyantika (Indonesia Emerging Literacy Education, 2024)
Objective: Globalization and rapid technological advancements demand that education evolve to incorporate digital literacy, essential for developing critical thinking skills. This research was conducted to describe the effect of optimizing digital literacy through the PBL model on the critical thinking skills of secondary school students. Method: This research used a Classroom Action Research model and was carried out in 3 cycles of four activities: planning, action, observation, and reflection. Results: The student's critical thinking skills significantly improved throughout PBL implementation. PBL encourages students to be active in solving real problems and allows them to apply digital literacy optimally. The strong correlation between digital literacy and critical thinking skills shows that both complement each other in evaluating and utilizing digital information effectively while honing critical judgment in problem-solving. These interrelated competencies strengthen the learning process, with a focus on problem-solving and in-depth analysis within the PBL framework. Novelty: This study evaluates the role of PBL in enhancing critical thinking via digital literacy in Society 4.0. It underlines the significance of technology in learning, evidencing its benefit to critical thinking, and offers recommendations for educators to utilize PBL and digital literacy to unlock student’s potential.